Kepercayaan dan Persepsi Risiko sebagai Penentu Minat Belanja Online Konsumen - Baderi, Baderi (Jurnal Informatika dan Bisnis, 2025)
This research aimed to examine how trust and perceived risk relate to consumers’ purchase intentions on online shopping platforms. A quantitative approach with a non-parametric correlational design was applied to assess the strength and direction of the association between these variables. The study was carried out from July to September 2025 and involved 134 active female undergraduate students enrolled in Digital Business programs across Jombang Regency, East Java. Female participants were selected as the study sample because they are generally more engaged in online shopping activities, making them suitable representatives of digital consumer behavior. Data were gathered using an online questionnaire adapted and validated from established research instruments. The collected data were analyzed using SPSS version 26, employing descriptive statistics and the Spearman’s rho correlation test due to the ordinal scale and non-normal distribution of the data. The findings revealed a significant positive correlation between consumer trust in online shopping platforms and purchase intention (p = 0.025), while perceived risk showed a significant negative correlation with purchase intention (p = 0.039). These results emphasize the importance of strengthening consumer trust and minimizing perceived risk as strategic efforts to enhance marketing effectiveness within the e-commerce industry.